2020
DOI: 10.21203/rs.3.rs-137207/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Which are factors determining a low COVID-19 mortality in society? High health expenditure and lower exposure of population to air pollution as critical factors for an effective strategy to cope with future pandemics similar to COVID-19

Abstract: One of the problems hardly clarified in the scientific field of Coronavirus Disease 2019 (COVID-19) is inter-related factors associated with a lower mortality of COVID-19 to design effective strategies to cope with unforeseen pandemic crises. The main goal of this study is to explain these factors determining a lower fatality rate of the Coronavirus disease 2019 (COVID-19) in society with a global analysis based on more than 160 countries worldwide. This study reveals a novel finding: countries with a low aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Relevant research on the outbreak of COVID-19 has paid attention to this matter. It has been found that a large number of bacteria and viruses are suspended in PM 2.5 , PM 10 , and other atmospheric particles in air pollution; that is, viruses such as the SARS-CoV-2 can be transmitted to the human body through biological aerosols [61]. First, this discovery should help policymakers realise that it is extremely important to reduce pollution sources as much as possible, because a clean natural environment can also reduce the burden of infectious [62] and other [11,12] diseases caused by air pollution.…”
Section: Environmental Protection Policies Should Be Combined With Th...mentioning
confidence: 99%
See 2 more Smart Citations
“…Relevant research on the outbreak of COVID-19 has paid attention to this matter. It has been found that a large number of bacteria and viruses are suspended in PM 2.5 , PM 10 , and other atmospheric particles in air pollution; that is, viruses such as the SARS-CoV-2 can be transmitted to the human body through biological aerosols [61]. First, this discovery should help policymakers realise that it is extremely important to reduce pollution sources as much as possible, because a clean natural environment can also reduce the burden of infectious [62] and other [11,12] diseases caused by air pollution.…”
Section: Environmental Protection Policies Should Be Combined With Th...mentioning
confidence: 99%
“…For a long time, compared with other aspects, politicians have regarded health as a secondary aspect of the government's action plan, thus redistributing the budget and paying more attention to those aspects that drive economic development [61]. An important way to improve health services is to improve health investment [66].…”
Section: Advanced Health Investment Is the Most Cost-effective Policy...mentioning
confidence: 99%
See 1 more Smart Citation